Da’wah Communication Strategy of Ustadz Ucay in Enhancing Religious Awareness and Understanding - Ahmad Sultoni Matondang (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − This study aims to analyze the da'wah communication strategies used by Ustadz Ucay in increasing religious awareness and understanding among the community. Da'wah as a process of religious communication requires effective communication strategies so that the conveyed messages can be well understood and accepted by the audience.   Method − This research uses a qualitative approach with a library research method by examining various scientific literatures related to da'wah communication, persuasive approaches, and the use of media in da'wah activities. The data analysis technique was conducted through content analysis of various literature sources to identify patterns and effective strategies of da'wah communication. Findings − The results of the study indicate that there are three main strategies that play an important role in improving public religious awareness and understanding. First, the strategy of delivering da'wah messages in an easily understandable manner through the use of simple, systematic, and contextual language so that religious messages can be received clearly by the audience. Second, the use of persuasive and humanistic approaches that emphasize empathetic, dialogical, and respectful communication toward the social conditions of the audience, thereby creating a harmonious relationship between the preacher and the congregation. Third, the utilization of media and interaction with the congregation, which allows the da'wah process to reach a wider audience, become more participatory, and adapt to technological developments. Therefore, communicative and contextual da'wah communication strategies can enhance the effectiveness of da'wah in building religious awareness and understanding within society.